Effect of Twist-Drill Craniostomy With Hollow Screws for Evacuation of Chronic Subdural Hematoma: A Meta-Analysis - Wei, Zeng; Jiang, Haixiao; Wang, Ying; Wang, Cunzu (Frontiers in Neurology, 2022)
Objective This study systematically reviews the clinical efficacy and safety of twist-drill craniostomy with hollow screws in chronic subdural hematoma treatment. Methods A computerized search of PubMed, Embase, Web of Science, Cochrane Library, World Health Organization International Trial Registry platform, CBM, CNKI, and Wanfang Database was performed to retrieve randomized controlled trials or case-control trials using twist-drill craniostomy (TDC) with hollow screws for the evacuation of chronic subdural hematoma from the date of databases' inception to July 2021. Two investigators independently screened the studies and extracted data in strict accordance with pre-established inclusion and exclusion criteria. RevMan 5.3 software or STATA was used for meta-analysis after evaluating the methodological quality of the included studies. Results A total of 4 randomized controlled trials and 16 case-control trials with a total of 2,536 cases were included. Results of the meta-analysis showed that the surgical success rate and postoperative recurrence rate of TDC with hollow screws were slightly higher compared to the burr hole craniostomy (BHC) group, but showed no statistical significance (RR = 1.03, P = 0.05; RR = 1.13, P = 0.50). However, subgroup analysis showed that the use of YL-1 needle had a higher success rate and lower recurrence rate (RR = 1.05, P = 0.02 < 0.05; RR = 0.584, P = 0.002), and TDC with hollow screws had a lower incidence rate of postoperative complications and postoperative acute intracranial hemorrhage compared with BHC, also revealing an overall shorter hospital stay (RR = 0.57, P = 0.0002 < 0.05; RR = 0.584, P = 0.027 < 0.05; WMD = −3.752, P < 0.001). However, the postoperative mortality rate was practically the same between the two groups (OR = 1.01, P = 0.95 > 0.05). Conclusion Twist-drill craniostomy with hollow screws is not inferior or superior to BHC in efficacy, and this strategy is safer and minimally invasive, which is reflected in a lower incidence of acute intracranial hemorrhage, overall complication rate, and length of hospital stay. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42021270835.